Test rig design to simulate ashlock valve erosion in coal gasification systems - Willmott, Simon Spencer (Centre for Materials Engineering, 2016)
The erosion of ashlock hopper valves in coal gasification systems, and the maintainance downtime resulting from this erosion, is a cause of considerable concern to the coal conversion industry. After an assessment of the factors considered relevant to solid particle erosion as presented in literature, a design for a laboratory test apparatus to closely simulate the in-service problem was proposed. A test rig prototype, reproducing service conditions of temperature, pressure and geometry, was constructed and preliminary testing conducted. Various problems impairing the efficient operation of the test facility became apparent and these, together with the proposed solutions and modifications to the prototype rig, are discussed. Both room temperature and elevated temperature (400°C) erosion tests were conducted on the hardfacing seat material presently used on site as well as a on selection of common engineering materials. Optical and scanning electron microscopy (SEM) studies revealed a close correlation between in-situ and laboratory erosion damage, suggesting that the test apparatus is a valid simulation of the service problem.